Design of a Web-Based Fashion Product Marketing Information System (Case Study on Eny Polokarto Convection) - Saputri, Bela; Naury, Chairullah; Pantjarani, Ari (Indonesian Journal of Information Technology and Computing (IMAGING), 2022)
The design of a website-based marketing information system at Eny Convection is the result of the author's daily observations as one of the worker of the Eny Convection Industry. Eny Convection is a home industry that is engaged in manufacture and sell fashion and its needs. A bussiness cannot be separated from marketing, which is a way to attract people's attention to a bussiness or product. Eny Convection it is only done through social media, it becomes an obstacle at Eny Convection that often customers have difficulty in finding information, and often curtomers experience disappointment because when looking for inventory quantities are not available. The purpose of this research is to create on online applicationÂ  that will be built by Eny Convection with data colection used bt interview, obserevation, documentation library research. Eny Convection product marketing which is producted with the concept of PHP (Personal Home Page). The results of the marketing are that the development system uses the waterfall system method, the system design Deamwevawer application or Sublime Text and MySQL as a database to improve the marketing Konveksi Eny. The conclusion of this research is that it able to improve marketing at Eny Convection in more professional way to market product and make it easier for customers to find product information available at Eny Convection.